Semiotic Interpretation of ”Imperfect: Karir, Cinta dan Timbangan” Film by Using Roland Barthes Theory - Yosephine Angelica Tarigan; Elisa Betty Manullang (Universitas Negeri Medan, 2022)
This study about the semiotic interpretation of “Imperfect: Karir, Cinta dan Timbangan” film with Roland Barthes Theory. This study aims to (a) find out the signs that found in “Imperfect: Karir, Cinta dan Timbangan” film and (b) describe how the signs interpreted in “Imperfect: Karir, Cinta dan Timbangan” film. This reasearch uses descriptive qualitative method. The data were taken from words and phrases which are collected from ‘Imperfect: Karir, Cinta dan Timbangan’ film script. The results shows that there were 15 signs found in Imperfect: Karir, Cinta dan Timbangan film. Timbangan (balance) as the most frequent signs was about 8 data such as: stranded whale; stairs vibration; power head waste; eating tissue; broccoli hair; remember your thigh; you are so fat ya, but it’s OK it’s fresh; and both of you are so different, even you are sisterhood, followed by Cinta (love) with 4 data namely: moles; stretch mark, reduce the rice; and use sunblock, and 3 data for Karir (career) such as pregnant; round face; and she is so old school. The signs includes in Karir (career) when it relates to the development, growth, and progress of someone’s job/profession. The signs that associate to Cinta (love) connects to the deepest someone’s emotional and interpersonal affection. The signs Timbangan (balance) that have a correlation with someone’s weight and physical condition or appearance. Timbangan (balance) were realized by the utterance that refers to physical condition and closely to mock. Cinta (love) associate to the word, gesture, or utterances that express a love or deepest personal affection. Karir (career) was described by a simple word to mock that closely sounds sarcastic and exaggerating.